Democratization, national identity, and foreign policy in Southeast Asia - Croissant, Aurel (Democratization, national identity and foreign policy in Asia, 2021)
This study suggests that the implementation of democratic procedures and practices in a number of Southeast Asian countries has helped to manage national identity problems, while the levels of quality of democracy have also been affected by issues of national identity. The chapter argues that the transition from authoritarian rule to electoral democracy (first transition) has often opened-up political space for democratizing national identities in Southeast Asia, whereas the lack of progress in the second transition, from democratically elected governments to liberal and fully consolidated democratic regimes, has complicated mutually shared agreement about identity with consequences in conflicts about their content and comprehensiveness as well as their impact on domestic and foreign policies.